2004
DOI: 10.1021/ma049864l
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Polymerization of 3,4-Ethylenedioxythiophene:  A Route to Highly Conducting Polymer Surface Layers

Abstract: A new synthetic route to poly-3,4-ethylenedioxythiophene (PEDT) with a conductivity exceeding 1000 S/cm is described. The method is based on base-inhibited vapor-phase polymerization, where a surface covered with ferric p-toluenesulfonate as oxidant mixed with a volatile base (pyridine) is exposed to 3,4-ethylenedioxythiophene (EDT) vapors. The base is added to suppress an acid-initiated polymerization of EDT, leading to a product with little or no conjugation. The product of the base-inhibited vapor-phase pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
346
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(361 citation statements)
references
References 15 publications
11
346
1
3
Order By: Relevance
“…S1). The guest MWNT aerogel sheet strips were drawn from special CNT forests that are drawable 24 , and the conducting polymer yarn guest was subsequently deposited by vapour phase polymerization (VPP), which is a well-known method for providing uniform coatings of highly conducting polymer layers on substrates 25 . In the present case, the coated substrate structure is three-dimensional, as the conducting polymer coats MWNTs and MWNT bundles within the host sheet.…”
Section: Resultsmentioning
confidence: 99%
“…S1). The guest MWNT aerogel sheet strips were drawn from special CNT forests that are drawable 24 , and the conducting polymer yarn guest was subsequently deposited by vapour phase polymerization (VPP), which is a well-known method for providing uniform coatings of highly conducting polymer layers on substrates 25 . In the present case, the coated substrate structure is three-dimensional, as the conducting polymer coats MWNTs and MWNT bundles within the host sheet.…”
Section: Resultsmentioning
confidence: 99%
“…18 The VPP method consists of coating the substrate with an oxidant dissolved in solution and exposure of the coated surface to appropriate monomer vapor. 19 This method is very useful in producing conductive thin membranes on substrates with highly controllable properties.…”
Section: Resultsmentioning
confidence: 99%
“…Winther-Jensen and West demonstrated the use of the FTS oxidant with pyridine as a weak base inhibitor during VPP to strengthen the electrical conductivity of PEDOT films. 18,25 Further studies employing imidazole to raise the pH of the oxidant also determined that, as the base evaporates from the oxidant, a more controlled polymerization was triggered. 15,26 Meanwhile, Fabretto et al suggested the role of water during the VPP process.…”
Section: 폴리머 제39권 제3호 2015년mentioning
confidence: 99%